- Al-Qur’an Perspective on Gender Equality in Community Empowerment Through Philanthropy during the 19th Pandemic: Al-Qur’an Perspective on Gender Equality in Community Empowerment Through Philanthropy - Nur Arfiyah Febriani; lilis fauziyah balgis (Direktorat Jenderal Bimbingan Masyarakat Islam, 2021)
This study aims to analyze the potential of women in philanthropic activities during the covid 19 pandemic which was carried out by the author as a member of Fatayat NU Bogor Regency. This is to erode the stereotype of women who are considered passive, receptive, and give up easily in dealing with life's problems. This study uses a descriptive qualitative approach by reviewing facts, expert opinions, interviews with sources, relevant theoretical studies and is equipped with the maudu'i interpretation method in analyzing verses related to philanthropy. This study found that women have the same potential as men in carrying out philanthropic activities. Fatayat Bogor Regency's philathropic activities are applied in the family, community, school and community organizations. Philanthropy activities are not only in worship activities such as zakat infaq and sadaqah, but also in mu'amalah activities such as in the economic and agricultural fields.